Functional Renal Reserve: Physiological Value of Renal Reserve and Substantiation of the Method of Its Determination - Hozhenko, A.I.; Kravchuk, A.V.; Sirman, V.M.; Nikitenko, O.P.; Romaniv, L.V. (KIDNEYS, 2022)
In the article the authors have substantiated and shown the mechanisms of functional renal reserve actuation and its physiological meaning. There is dwelt the method of functional renal reserve determination. It was tested by the authors by the means of water-salt load. Its high diagnostic value has been proved as well.